Comparative outcomes of inpatients with lung collapse managed by bronchoscopic or conservative means. Issue 1 (26th August 2019) - Toolsie, Omesh Gopal; Adrish, Muhammad; Zaidi, Syed Arsalan Akhter; Diaz-Fuentes, Gilda
Abstract : Background: Although the incidence and prevalence of atelectatic lung collapse is unknown, such events are common among inpatients, and there are no guidelines for optimally instituting bronchoscopic techniques. The aim of this study was to evaluate the outcomes of patients with complete or near-complete lung collapse managed via interventional flexible fibreoptic bronchoscopy or a conservative approach. Methods: Retrospective analysis of all adult patients admitted to BronxCare Health System between January 2011 and October 2017 with a diagnosis of lung collapse/atelectasis. The primary outcome was radiological resolution. Timing of bronchoscopy relative to radiological resolution and mortality served as secondary outcomes. Results: Of the 177 patients meeting inclusion criteria, 149 (84%) underwent bronchoscopy and 28 (16%) were managed through conservative measures only. A significantly greater number of patients in the bronchoscopy group achieved complete or near-complete resolution on chest X-ray, compared with the conservative group (p=0.007). Timing of bronchoscopy had no impact on the rate of radiological resolution, and mortality in the two groups was similar. New endobronchial malignancies were identified in 21 patients (14%). Conclusions: Our data support the central role of bronchoscopy in instances of complete or near-complete lung collapse, ensuring better radiological outcomes. Judicious use of conservative management is warranted to avoid missing significant pathology. A prime consideration in this setting is obstructive malignancy.